Dynamic role of gastric stem cells and chief cells in precancerous lesions of gastric cancer: global knowledge mapping and emerging trends based on bibliometric analysis from 2004 to 2024 - Wang, Chen; Zhou, Lijie; Wang, Yangang (Frontiers in Oncology, 2025)
BackgroundGastric stem cells (GSCs) and chief cells are vital for maintaining gastric epithelial homeostasis. However, under pathological conditions, these cells undergo significant functional changes, contributing to the progression of precancerous lesions of gastric cancer (PLGC). Dysregulation of key signaling pathways such as WNT, NF-κB, and YAP leads to aberrant cellular behaviors, which are implicated in the early stages of gastric carcinogenesis. This study aimed to elucidate the roles of GSCs and chief cells in maintaining gastric epithelial integrity, their contributions to the development of precancerous lesions, and the molecular mechanisms that regulate their behavior during disease progression.MethodsThe study integrated bibliometric analysis, pathfinding, and data visualization using tools such as CiteSpace, VOSviewer, and R software. Functional enrichment of target genes was analyzed using KEGG and GO databases. The study focused on gastric cell changes, including differentiation, dedifferentiation, and signaling pathway activation, within the context of GSC and chief cell plasticity. Molecular markers and pathway-specific mechanisms were analyzed to clarify their contributions to gastric precancerous lesions.ResultsData from the WoSCC database from 2004 to 2024 showed a steady increase in publications on “PLGC-gastric stem cells” and “PLGC-chief cells,” with the United States, China, and Japan leading in publication volume. International cooperation was evident, particularly with Canada playing a central role in academic exchanges. Key terms included stem cells, intestinal chemotaxis, and cancer, with recent focus on spasmolytic polypeptide-expressing metaplasia.ConclusionThe dynamic interactions between GSCs and chief cells are fundamental to gastric homeostasis and disease progression. GSCs primarily drive chronic inflammation-induced metaplasia and dysplastic changes, while chief cells facilitate acute epithelial repair through dedifferentiation. These findings highlight potential therapeutic targets and emphasize the importance of regulating dysregulated pathways to prevent gastric cancer. The research results will guide future studies in the fields of “PLGC-gastric stem cells” and “PLGC-chief cells,” focusing on the spatiotemporal dynamics of each cell type under various injury and inflammatory conditions, as well as identifying early biomarkers of cellular changes for timely intervention.